Inhibition of HMGB1/RAGE axis suppressed the lipopolysaccharide (LPS)-induced vicious transformation of cervical epithelial cells. Issue 1 (1st January 2021) - You, Lifang; Cui, Hongyin; Zhao, Fen; Sun, Huier; Zhong, Huanxin; Zhou, Guoli; Chen, Xuejun
ABSTRACT: The chronic inflammation operates as one of the critical causes of cervical cancer. Activation of HMGB1/RAGE axis could induce the inflammation and lead to multiple types of cancer. However, whether the HMGB1/RAGE axis could affect the development of cervical cancer by regulating the inflammation is unclear. Here, we stimulated normal cervical epithelial cells with lipopolysaccharide (LPS). Next, the expression of RAGE in these cells was suppressed by the RAGE inhibitor. CCK-8 and wound healing assays were performed to detect the proliferation and invasion. To determine how inflammatory factors (IL-1β, IL-6 and TNF-α) expressed in supernatant of these cells, ELISA was conducted. Western blotting was used for the detection of the expression of pyroptosis-related proteins (NLRP3 and caspase4). It was found that stimulation of LPS enhanced the proliferation and invasion of normal cervical epithelial cells. The expression of inflammatory factors (IL-1β, IL-6 and TNF-α) in these cells was promoted as well. Application of RAGE inhibitor abolished the efficacy of LPS on these cells. Furthermore, LPS promoted the expression of NLRP3 and caspase4 in these cells while RAGE inhibitor exerted suppressive effects on the expression of these proteins. In summary, LPS-induced inflammation of normal cervical epithelial cells resulted in the malignant transformation of these cells by activating HMGB1/RAGE axis.